The High Performance Management Model: From Olympic and professional to University sport in the United States - Smith, J.; Smolianov, P. (The Sport Journal, 2016)
This exploratory study of the High Performance Model of Sport Management examines the model`s origins and where these ideas were first applied in the sports industry. This review discusses the evolution of its use in high level sport, and the successes incurred in systems utilizing the model. The investigation discusses the recent spreading of the model throughout Olympic and professional sports organizations throughout the world, where High Performance concepts are being studied and implemented into professional sports franchises in the United States as well as American universities. This study focuses on a particular ingredient important to the success of the High Performance Model at the "meso" and "micro" levels of implementation. This central step is the establishment of an integral operational position titled "High Performance Director" or "High Performance Manager". The duties, responsibilities, areas of expertise, and traits necessary for success are reviewed and discussed. The inquiry explores the natural evolution of the High Performance Model into the industry of NCAA Division I athletics, where implementation is occurring at the University of Northern Iowa (UNI). Here, the Smith and Smolianov High Performance Model is being applied within UNI Athletics, using strength and conditioning as the median for operation. The infrastructure is being created and organized for proper application of the model. The study looks at how technology is being used to help monitor, track, and adjust training protocols as well as assist in the proper development of athletes. The review will indicate tactics used for selling the concepts internally, within an NCAA athletic, as well as an educational setting, exposing key players and supports, explaining the connection between these pillars of support and the importance of creating synergy, transparency, and an environment of effective communication. This work is the first in a series of exploratory reviews and future research to be conducted by the authors, who are reporting the current, ongoing case study, within UNI`s NCAA athletics/education program.